The effect of using the problem solving strategy on educational psychology achievement among students of the faculties of education - Sabar Mahdi saleh; prof. Dr.adela ali naji (Journal of College of Education, 2024)
The duration of the experiment lasted a full academic year for the academic year (2022-2023), and the research tools consisted of an achievement test prepared by the researcher consisting of (40) items, including (30) multiple-choice items and (10) items of essay questions. The researcher verified the validity of the tool by presenting it to a group of experts and arbitrators in the methods of teaching, education, measurement and evaluation, and the stability, difficulty and distinction of the achievement test items only. After applying the tool and processing the data statistically by using the second test for two independent samples, the results resulted in the superiority of the experimental group that studied according to the educational-learning program over the students of the control group who studied the same subject according to the vocabulary of (problem Solving strategy ) in the achievement test in educational psychology, and to know the size of the effect The independent variable (right) education. Learning according to the cognitive memory model in the dependent variable (achievement) educational psychology subject For the students of the second grade / Department of Educational and Psychological Sciences in the Faculties of Education), Cohen’s value was extracted by means of the square of his verse, and thus, the size of the effect of the independent variable is high, as it reached (1,305) in the achievement. In the light of the research results, the researcher reached a number of conclusions, recommendations and proposals .